Current developments and prospects on human metapneumovirus vaccines - Verónica Araceli Márquez-Escobar (Taylor & Francis Group, 2017)
Introduction: Human metapneumovirus (hMPV) has become one of the major pathogens causing acute respiratory infections (ARI) mainly affecting young children, immunocompromised patients, and the elderly. Currently there are no licensed vaccines against this virus. Areas covered: Since the discovery of hMPV in 2001, many groups have focused on developing vaccines against this pathogen. This review presents the outcomes and perspectives derived from preclinical studies performed in cell cultures and animals as well as the only candidate that has reached evaluation in a clinical trial. Limitations of the current vaccine candidates are discussed and perspectives for the development of plant-based vaccines are analyzed. Expert commentary: Several hMPV vaccine candidates are under development with the potential to progress into clinical trials. In parallel, the molecular farming field offers new opportunities to generate innovative vaccines that will offer several advantages in the fight against hMPV.